Los depósitos uraníferos en rocas sedimentarias en la República Argentina - Stipanicic, Pedro N.; Baulies, O. L.; Rodrigo, Félix; Martínez, C. G. M. (Comisión Nacional de Energía Atómica; Argentina, 1960)
Fil: Stipanicic, Pedro N. Comisión Nacional de Energía Atómica; Argentina